Quaternary Ammonium Polyethyleneimine: Antibacterial Activity. (29th June 2010) - Yudovin-Farber, Ira; Golenser, Jacob; Beyth, Nurit; Weiss, Ervin I.; Domb, Abraham J.
Abstract : Quaternary ammonium polyethyleneimine- (QA-PEI-) based nanoparticles were synthesized using two synthetic methods, reductive amination and N-alkylation. According to the first method, QA-PEI nanoparticles were synthesized by cross-linking with glutaraldehyde followed by reductive amination with octanal and further N-methylation with methyl iodide. The second method is based on crosslinking with dialkyl halide followed by N-alkylation with octyl halide and further N-methylation with methyl iodide. QA-PEI nanoparticles completely inhibited bacterial growth (>10 6 bacteria), including both Gram-positive, that is, Staphylococcus aureus at 80 μ g/mL, and Gram-negative, that is, Escherichia coli at 320 μ g/mL. Activity analysis revealed that the degree of alkylation and N-methylation of the QA-PEI nanoparticles plays a significant role in antibacterial activity of the reagent. The most potent compound was octyl alkylated QA-PEI alkylated at 1 : 1 mole ratio (primary amine of PEI monomer units/alkylating agent). Also, cytotoxicity studies on MAT-LyLu and MBT cell lines were performed with QA-PEI nanoparticles. These findings confirm previous reports that polycations bearing quaternary ammonium moieties inhibit bacterial growth in vitro and have a potential use as additives in medical devices which need antibacterial properties.